STRATEGI MENUMBUHKAN MINAT BELAJAR SISWA MELALUI PENDEKATAN DEEP LEARNING - Arif, Mohammad Nur; Parawansyah, Muhammad Isya; Huda, Fiqi Haikal; Zulfahmi, Muhammad Nofan (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2025)
This article discusses strategies to foster students' interest in learning through deep learning approach in the context of education, interest in learning is a crucial factor that affects students' motivation and learning outcomes. A deep learning approach that can emphasize in-depth understanding and interconnectedness between concepts and is expected to increase student engagement in the learning process. Through the application of this method, students are invited to actively participate in discussion, collaboration, and creative exploration of the material, so that they feel more connected to what they are learning. This article also presents various techniques and activities that can be applied by educators to implement deep learning strategies in the classroom. By using project-based approaches, case studies and problem-based learning, students are encouraged to think critically and develop analytical skills. The results of implementing this strategy show a significant increase in students' interest in learning which is reflected in active participation and better academic achievement. This research is expected to contribute to the development of more effective and engaging teaching methods in the Education environment.